2023
DOI: 10.3390/s24010037
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers in Cancer Detection, Diagnosis, and Prognosis

Sreyashi Das,
Mohan Kumar Dey,
Ram Devireddy
et al.

Abstract: Biomarkers are vital in healthcare as they provide valuable insights into disease diagnosis, prognosis, treatment response, and personalized medicine. They serve as objective indicators, enabling early detection and intervention, leading to improved patient outcomes and reduced costs. Biomarkers also guide treatment decisions by predicting disease outcomes and facilitating individualized treatment plans. They play a role in monitoring disease progression, adjusting treatments, and detecting early signs of recu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(9 citation statements)
references
References 387 publications
0
9
0
Order By: Relevance
“…Specifically, the interaction diagram illustrated that these RNA splicing and nucleic acid-templated transcription-related proteins possessing dopaminylation involved many key regulators in cancer development, such as transcription factors Sp1 (SP1), serine/threonine-protein kinase mTOR (MTOR), tyrosine-protein kinase ABL1 (ABL1), and heterogeneous nuclear ribonucleoproteins (hnRNPs), which are druggable targets for cancer therapies. Additionally, among these dopaminylated proteins, the transcriptional repressor protein YY1 and Aly/REF export factor (ALYREF) have been identified as potential tumor biomarkers for both diagnosis and prognosis . In the cancer-related cluster (Figure A), there are also numerous proteins playing key roles in carcinogenesis, which include the splicing factor polyglutamine-binding protein 1 (PQBP1), small nuclear ribonucleoprotein polypeptide C (SNRPC), small nuclear ribonucleoprotein polypeptide A (SNRPA), RNA-binding protein FUS (FUS), histone-arginine methyltransferase CARM1 (CARM1), splicing factor proline- and glutamine-rich (SFPQ) protein, nuclear receptor coactivator 3 (NCOA3), and nuclear pore glycoprotein p62 (NUP62) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the interaction diagram illustrated that these RNA splicing and nucleic acid-templated transcription-related proteins possessing dopaminylation involved many key regulators in cancer development, such as transcription factors Sp1 (SP1), serine/threonine-protein kinase mTOR (MTOR), tyrosine-protein kinase ABL1 (ABL1), and heterogeneous nuclear ribonucleoproteins (hnRNPs), which are druggable targets for cancer therapies. Additionally, among these dopaminylated proteins, the transcriptional repressor protein YY1 and Aly/REF export factor (ALYREF) have been identified as potential tumor biomarkers for both diagnosis and prognosis . In the cancer-related cluster (Figure A), there are also numerous proteins playing key roles in carcinogenesis, which include the splicing factor polyglutamine-binding protein 1 (PQBP1), small nuclear ribonucleoprotein polypeptide C (SNRPC), small nuclear ribonucleoprotein polypeptide A (SNRPA), RNA-binding protein FUS (FUS), histone-arginine methyltransferase CARM1 (CARM1), splicing factor proline- and glutamine-rich (SFPQ) protein, nuclear receptor coactivator 3 (NCOA3), and nuclear pore glycoprotein p62 (NUP62) …”
Section: Resultsmentioning
confidence: 99%
“…Additionally, among these dopaminylated proteins, the transcriptional repressor protein YY1 and Aly/REF export factor (ALYREF) have been identified as potential tumor biomarkers for both diagnosis and prognosis. 26 In the cancer-related cluster (Figure 4A), there are also numerous proteins playing key roles in carcinogenesis, 27 which include the splicing factor polyglutamine-binding protein 1 (PQBP1), 28 small nuclear ribonucleoprotein polypeptide C (SNRPC), 29 small nuclear ribonucleoprotein polypeptide A (SNRPA), 29 RNA-binding protein FUS (FUS), 30 histone-arginine methyltransferase CARM1 (CARM1), 31 splicing factor proline-and glutamine-rich (SFPQ) protein, 28 nuclear receptor coactivator 3 (NCOA3), 32 and nuclear pore glycoprotein p62 (NUP62). 33 Intriguingly, even though the colon cancer cell line was utilized as a model in this research, within the cluster of identified 176 dopaminylated proteins that are associated with RNA splicing and nucleic acid-templated transcription, a subset was discovered to be linked to nervous system development (Figure 4B), which further highlighted the essential role of dopamine in neurodevelopment as a key neurotransmitter.…”
Section: Journal Ofmentioning
confidence: 99%
“…This suggests that MKi67 could be an important biomarker for cancer progression and therapeutic outcomes. Also, new studies have shown that high MKi67 levels may be a sign of aggressive disease progression in people who are being treated with first-line EGFR-TKIs [32]. Recently, another study reported that a high expression of MKi67 may indicate the aggressive progression to the first-line EGFR-TKI.…”
Section: Discussionmentioning
confidence: 99%
“…In the realm of biomedical research, biomarkers play a crucial role as indicators of biological processes, disease progression, and treatment efficacy by providing insights into the underlying molecular mechanisms of cancer development and progression, as well as other disorders [12][13][14]. Therefore, the identification and validation of reliable biomarkers hold significant promise for improving cancer diagnoses, prognoses, and therapeutic Biomolecules 2024, 14, 488 2 of 14 outcomes.…”
Section: Introductionmentioning
confidence: 99%